Faktor Faktor Penyebab Penundaan Operasi Elektif Di Instalasi Bedah Sentral Rsud Banyumas - Nasrulloh, Amin; Asiandi, Asiandi; Elsanti, Devita; H, Dyah Yulistika (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Background: Data shows that there were 655 (22.53%) operational delays out of 2907 operations during June – December 2022. The percentage of operational delays is still much higher than the target recommended by KARS on the National Quality Indicator of postponement of elective surgery, namely no more of 5%. There are several main factors that cause delays in operations including patient factors, staff factors, facility factors, and administrative factors. This fact is very concerning considering the quality of hospital services plays an important role in the level of patient satisfaction in the midst of increasingly fierce hospital competition. Objective: To find out the factors causing delays in elective surgery at the Central Surgical Installation of Banyumas Hospital. Methods: This study used a retrospective observational analytic method with a cross-sectional approach. The sampling technique used was cluster sampling which was taken randomly from June to December with a total sample of 248 ERM. The analysis used is Logistic Regression. Results: There is a significant relationship between patient factors (p 0.045; OR 0.036) and staff factors (p 0.037; OR 0.038). Conclusion: The staff factor is the most dominant factor affecting delays in operations at the Central Surgical Installation of Banyumas Hospital.